1998
DOI: 10.1152/ajpcell.1998.275.5.c1224
|View full text |Cite
|
Sign up to set email alerts
|

Partial agonists and antagonists reveal a second permeability state of human lymphocyte P2Z/P2X7channel

Abstract: Extracellular ATP is known to trigger apoptosis of thymocytes and lymphocytes through a P2Z receptor at which ATP is a partial agonist, giving only 70% of the maximum response of 3′- O-(4-benzoyl)benzoyl-adenosine 5′-triphosphate (BzATP), a full agonist. This cytolytic receptor and its associated ion channel are Ca2+ (and Ba2+) selective but also pass molecules up to the size of ethidium cation (314 Da). RT-PCR showed identity between lymphocyte P2Z and the hP2X7 gene recently cloned from human monocytes. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
1

Year Published

2001
2001
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 40 publications
8
68
1
Order By: Relevance
“…At 10.0 M, EIPA was toxic as seen by the appearance of apoptotic cells with subdiploid DNA content (Figure 6b). 75 As shown before, POH treatment reduced the proportion of cells in S phase and caused apoptosis (Figure 6e), while TPA reversed the POH-mediated apoptosis (Figure 6f). The ability of TPA to protect the cells from POH-mediated apoptosis was abrogated by EIPA.…”
Section: Figuresupporting
confidence: 72%
“…At 10.0 M, EIPA was toxic as seen by the appearance of apoptotic cells with subdiploid DNA content (Figure 6b). 75 As shown before, POH treatment reduced the proportion of cells in S phase and caused apoptosis (Figure 6e), while TPA reversed the POH-mediated apoptosis (Figure 6f). The ability of TPA to protect the cells from POH-mediated apoptosis was abrogated by EIPA.…”
Section: Figuresupporting
confidence: 72%
“…As a control, RNA samples were also subjected to the first strand cDNA preparation protocol without reverse transcriptase. Primers were based on the reported sequences of the human P2Y 1 , P2Y 2 , P2Y 4 , and P2X 7 receptors (Parr et al, 1994;Communi et al, 1995;Ay yanathan et al, 1996;Rassendren et al, 1997), and the primers for P2Y 2 , P2Y 4 , and P2X 7 have been published previously (Gorodeski et al, 1998;Merten et al, 1998;Wiley et al, 1998): P2Y 1 forward, 5Ј-GAC TTC TTG TAC GTG C TG AC T C T-3Ј; and reverse, 5Ј-GAC C TC TTG TCA CC T GAT ACG TG-3Ј; P2Y 2 forward, 5Ј-C TC TAC TTT GTC ACC ACC AGC GCG-3Ј; and reverse, 5Ј-TTC TGC TCC TAC AGC CGA ATG TCC -3Ј; P2Y 4 forward, 5Ј-ATC C TG CCA CCC TCA C TT C TC C -3Ј; and reverse, 5Ј-AGG CGA GAA GAC GAC TGT GC -3Ј; and P2X 7 forward, 5Ј-AC T CC T AGA TCC AGG GAT AGC C -3Ј; and reverse, 5Ј-TCA C TC TTC GGA AAC TC T TTC C-3Ј. Conditions applied for PCR were as follows: 95°for 5 min, followed by 31 cycles of 1 min 95°C, 1 min 64.4°C (P2Y 1 , P2Y 2 , P2X 7 ) or 61.8°C (P2Y 4 ), and 1 min 72°C, followed by 72°C for 7 min.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas short stimulation of the receptor by ATP is believed to facilitate the passage of cations and promote proliferation, strong or prolonged stimulation enables the passage of larger molecules that may act as a trigger for apoptosis. [3][4][5] A common singlenucleotide polymorphism (SNP) within the P2X7 gene has been described in exon 13 (nucleotide 1513A to C), which results in the substitution of glutamic acid at amino-acid position 496 by alanine (E496A). This polymorphism occurs in the region of the gene that encodes the carboxy-terminal tail of the protein, a structure that controls the permeability properties of the P2X7 receptor, 4 and biochemical studies have demonstrated that homozygosity for the C allele (C / C) leads to almost complete loss of P2X7 function, whereas heterozygosity (A / C) give a function that is half that of cells with the germline (A / A) P2X7 sequence.…”
Section: Introductionmentioning
confidence: 99%